Pengaruh Kepemimpinan Kepala PAUD dan Kompetensi Guru terhadap Kinerja Guru - Royani, Ida; Fitria, Happy; Rohana, Rohana (Journal of Innovation in Teaching and Instructional Media, 2020)
This study aimed to determine the influence of principal leadership of PAUD and teachers’ competence on the performance of PAUD teachers in Sembawa Subdistrict. Data in this study were collected through distributing the questionnaires to respondents. The results of the questionnaire were analyzed by using multiple regression analysis through t-test, F-test, and the coefficient of determination. Population of the study was 87 PAUD teachers in Sembawa Subdistrict. The sample in this study was 57 PAUD teachers in Sembawa sub-district. Research results showed: 1) there was a positive and significant influence of principal leadership of PAUD on teachers’ performance; 2) there was a positive and significant influence of teachers’ competence on teachers’ performance; 3) there was a significant influence simultaneously of principal leadership of PAUD and teachers’ competence on the performance of PAUD teachers in Sembawa sub-district Banyuasin.